Preventing Cesarean Birth in Women with Obesity: Influence of Unit‐Level Midwifery Presence on Use of Cesarean among Women in the Consortium on Safe Labor Data Set. (28th August 2019) - Carlson, Nicole S.; Breman, Rachel; Neal, Jeremy L.; Phillippi, Julia C.
Abstract : Introduction: Maternal obesity is associated with slow labor progression and unplanned cesarean birth. Midwives use fewer medical interventions during labor, and the women they care for have lower cesarean birth rates, compared with low‐risk, matched groups of women cared for by physicians. The primary aim of this study was to examine associations between midwifery unit‐level presence and unplanned cesarean birth in women with different body mass index (BMI) ranges. Unit‐level presence of midwives was analyzed as a representation of a unique set of care practices that exist in settings where midwives work. Methods: A retrospective cohort study was conducted using Consortium on Safe Labor data from low‐risk, healthy women who labored and gave birth in medical centers with (n = 9795) or without (n = 13, 398) the unit‐level presence of midwives. Regression models were used to evaluate for associations between unit‐level midwifery presence and 1) the incidence of unplanned cesarean birth and 2) in‐hospital labor durations with stratification by maternal BMI and adjustment for maternal demographic and pregnancy factors. Results: The odds of unplanned cesarean birth among women who gave birth in centers with midwives were 16% lower than the odds of cesarean birth among similar women at who gave birth at centers without midwives (adjusted odds ratio, 0.84; 95% CI, 0.77‐0.93). However, women whose BMI was above 35.00 kg/m 2 at labor admission had similar odds of cesarean birth, regardless of unit‐level midwifery presence. In‐hospital labor duration prior to unplanned cesarean was no different by unit‐level midwifery presence in nulliparous women whose BMI was above 35.00 kg/m 2 . Discussion: Although integration of midwives into the caregiving environment of medical centers in the United States was associated with overall decrease in the incidence of cesarean birth, increased maternal BMI nevertheless remained positively associated with these outcomes.